Pathways of "rural development": an analysis of peritonormative proposals - Gameiro, Mariana Bombo Perozzi (Universidade Federal Rural do Rio de Janeiro, 2016)
Conceptual and operational definitions on ruralities have changed through time. With them, theoretical normative and political proposals for rural development have also changed. This article reviews the international and national literature to briefly introduce the multiple notions of the term development, as well as its ideological use. After that, it deals with rural development models, characterizing the main elements that arise in expert discourses on the subject. Discussing the contemporary debate on rural development, the article highlights the incorporation of the conceptions of sustainability and territoriality, with decentralized and participatory methodologies. These paths of multiple ideas that involve rural development are analyzed under contemporary sociological theories, mainly Anthony Giddens’ concept of expert system. It is understood, therefore, that strategically placed agents reflexively regulate global conditions of reproduction change or continuity of social systems, fomenting “space-time distanciated” relations.